1993
DOI: 10.1017/s0033291700028397
|View full text |Cite
|
Sign up to set email alerts
|

Reduced total complement haemolytic activity in schizophrenic patients

Abstract: SynopsisSerum concentrations of the third and fourth components of the complement system and total complement haemolytic activity were measured in 167 psychiatric patients. Total complement haemolytic activity was decreased in chronic schizophrenic patients as compared to healthy controls and bipolar patients. The relatively diminished total haemolytic activity was not attributable to drug treatment. It is not clear if the reduced total haemolytic activity is an epiphenomenon or related to the involvement of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 9 publications
0
24
1
1
Order By: Relevance
“…Initial attention was focused on complement total hemolytic activity, to which classical pathway activity contributes about 85%. Spivak et al 63 reported a decrease in complement total hemolytic activity in schizophrenic patients vs. controls, while a year later a Japanese group reported no difference. 64 More recent studies suggest that in schizophrenia there is a modest increase in complement total hemolytic activity (CH50), although neither study reached statistical significance.…”
Section: Complement In Schizophreniamentioning
confidence: 97%
See 2 more Smart Citations
“…Initial attention was focused on complement total hemolytic activity, to which classical pathway activity contributes about 85%. Spivak et al 63 reported a decrease in complement total hemolytic activity in schizophrenic patients vs. controls, while a year later a Japanese group reported no difference. 64 More recent studies suggest that in schizophrenia there is a modest increase in complement total hemolytic activity (CH50), although neither study reached statistical significance.…”
Section: Complement In Schizophreniamentioning
confidence: 97%
“…Maes et al 71 showed high C4 concentration in plasma of nonmedicated schizophrenic patients that is not reflected in the results of other groups. 62,63,72 In a recent correlation study on the relationship between acute phase proteins and psychopathology in paranoid schizophrenia, serum levels of C3 and C4 were suggested as biological markers of acute negative symptoms of paranoid schizophrenia. 76 While no item of the positive scale of the PANSS (Positive and Negative Syndrome Scale) significantly correlated with the levels of the C3 and C4, three of the seven items of the negative scale show positive correlations with the levels of these proteins.…”
Section: Complement In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite possible immune involvement, the role of the complement system in schizophrenia has not been widely explored. Results of a few studies on the evaluation of complement classical and lectin pathway activation in schizophrenia are conflicting (Spivak et al 1993;Shcherbakova et al 1999;Hakobyan et al 2005;Mayilyan et al 2006). The data obtained on the complement C4 and, in particular, on C4A and C4B, in schizophrenia are also contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also suggest that acute depression, schizophrenia and mania are accompanied by an acute phase protein response. Such studies have shown alterations in haptoglobin, complement, C-reactive proteins (CRP) and immunoglobulins amongst others (Balaita et al, 1992;Hornig et al, 1998;Ohaeri et al, 1993;Tudorache et al, 1991;Spivak et al, 1993;Maes et al, 1997Maes et al, , 1999Song et al, 1994). Most of these studies concentrated on depressed patients, schizophrenics and patients with affective disorders.…”
Section: Introductionmentioning
confidence: 99%